Analysis on Loose Circle of Surrounding Rock of Large Deformation Soft-Rock Tunnel - Rui Wang; Yiyuan Liu; Xianghui Deng; Yu Zhang; Xiaodong Huang; Xiao Ding (Advances in Civil Engineering)
With the rapid development of tunnel construction in China, deep buried and long tunnel projects are emerging in areas with complex engineering geological conditions and harsh environment, and thus large deformation of tunnels under conditions of high in situ stress and soft rock becomes increasingly prominent and endangers engineering safety. Therefore, it is of great significance to control the deformation and improve the stability of surrounding rock by analyzing the thickness and distribution law of loose circle according to the unique mechanical properties and failure mechanism of surrounding rock of large deformation soft-rock tunnel. Based on unified strength theory, this paper deduces the radius calculation formula of the loose circle by considering the influence of intermediate principal stress. Furthermore, the theoretical calculations and field tests of the loose circle in the typical sections of grade II and III deformation of Yuntunbao tunnel are carried out, and the thickness and distribution law of loose circle of surrounding rock of large deformation soft-rock tunnel is revealed. The results show that the formula based on the unified strength criterion is applicable for a large deformation tunnel in soft rock.